Upaya Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran PPKn melalui Penggunaan Media Konkret di Kelas VI SDN 067240 Medan Tembung - Mutia Fatihah; Zainal Aziz; Rahmat Nauli Hasibuan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to improve the mathematics learning outcomes of fourth-grade students of SDN 067240 through the use of MATPAS (Market Mathematics) teaching media. The background of this study is based on the low learning outcomes of students in understanding the concept of adding whole numbers due to the learning approach that is still abstract and less contextual. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. The subjects of the study were 15 fourth-grade students of SDN 067240. Data were collected through observation, learning outcome tests, and documentation, then analyzed descriptively quantitatively. The results showed that there was an increase in student learning completeness from 13.4% in the initial test to 33.4% in cycle I, and increased significantly to 86.7% in cycle II. The application of MATPAS media has been proven to increase students' motivation, involvement, and understanding of mathematics material contextually. Thus, MATPAS media is effectively used as an innovative alternative in mathematics learning in elementary schools.